The Impact Of Mathematical Writing On Mathematical Problem Solving Skills And Metacognition Among The First Year University Students - Betsy Lee, Guat Poh (2019)
This study focuses on mathematical writing as a mode of developing mathematical problem solving skills and metacognition among thirty Foundation in Engineering students. These students participated in a series of mathematical writing sessions to solve 15 mathematical problems for five weeks. Qualitative and quantitative data were collected including the students‘ written responses in mathematical writing workbook, their performance in a problem solving assessment, their self-report about metacognition progression as well as their perceptions about mathematical writing. An exploratory case study analysis was applied to examine these data. This study was based on a purposive sample of thirty Foundation in Engineering students as the subject of the case. The findings showed that students’ effort in mathematical writing impacted the problem solving actions taken at each problem solving phase.